Application Of Hospital Environmental Accounting: Alfred Schutz's Phenomenological Perspective - Aditya Fermana; Sabaruddin, Sabaruddin; Tarmizi, M.Irfan (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
The aim of the research carried out is to find out how environmental accounting standards are in efforts to prevent waste at the South Tangerang City General Hospital. The data collection methods and techniques used in this research were descriptive qualitative methods and direct interviews with the Waste Water Management Installation section and the accounting section related to environmental management costs. The data used comes from documentation or internal hospital data. Combining Schutz's phenomenological perspective, the data analysis stage includes interpretation, subjectivity and thematic analysis. Alfred Schutz's phenomenology is one of the important thoughts of phenomenology as a philosophical movement. At the same time, clarify the research object of social awareness in the development of social science awareness. From the research results, it was found that the South Tangerang city general hospital has managed its waste well and has carried out accounting treatment stages for environmental management costs and recorded environmental costs in goods and services expenses. With this research, it is hoped that the South Tangerang City General Hospital will implement environmental accounting better. Key words: Environmental Accounting, Hospital Waste, WWTP processing and Alfred Schutz's phenomology